Specifics of theological questions in literature: sin in the texts of Aidas Marčėnas - Vaišvilaitė, Radvyda (Literatūra, 2007)
The problem of this article arise from the challenges of interdisciplinary study of literature and theology – how to find a scientifically acceptable way of representing theological questions in literature, preserving the autonomy and at the same time highlighting common dialogically-based points of view of these two fields. The theological point of view to literature is based on its interest in the metaphorical, symbolical and image-based language of literature, which can express the deepest existential questions and transcendental dimensions of human essence. Literary theory deals with its autonomy and its connections with other fields of humanities: ethics, politics, and religion. Theological questions in literature might be viewed as individual religious experiences expressed in text and understood as representations of feelings and views that might be understood and perceived as common experience. Theological questions in literature are based on the specifics of the literary language of images and poetic language. Theological questions in literature also arise from its esthetic value and esthetic language. One of the methodological possibilities to deal with challenges of this interdisciplinary field might be to research what theological questions are, and how these questions arise in literature. Sin and guilt in the poetry of Aidas Marčėnas is reflected as individual and subjective theological question very much related with the understanding of human existence and creative nature.